Will seizure control improve by switching from the modified Atkins diet to the traditional ketogenic diet? - Eric H. Kossoff; Jennifer L. Bosarge; María J. Miranda; Adelheid Wiemer‐Kruel; Hoon‐Chul Kang; Heung Dong Kim (2010)
It has been reported that children can maintain seizure control when the ketogenic diet (KD) is transitioned to the less-restrictive modified Atkins diet (MAD). What is unknown, however, is the likelihood of additional seizure control from a switch from the MAD to the KD. Retrospective information was obtained from 27 patients who made this dietary change from four different institutions. Ten (37%) patients had ≥10% additional seizure reduction with the KD over the MAD, of which five became seizure-free. The five children who did not improve on the MAD failed to improve when transitioned to the KD. A higher incidence of improvement with the KD occurred for those with myoclonic-astatic epilepsy (70% vs. 12% for all other etiologies, p = 0.004), including all who became seizure-free. These results suggest that the KD probably represents a "higher dose" of dietary therapy than the MAD, which may particularly benefit those with myoclonic-astatic epilepsy.